The Optimization of Bioactive Compounds Continuous Extraction Conditions from Phaleria macrocarpa Fruit by Percolation Method - Susiana Prasetyo (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Crown of god (Phaleria macrocarpa) one of many native Indonesia medicinal plants, posseses with a great potential as natural preservative, food suplement, and medicine due to its high bioactive compounds, especially antioxidant content. Despite of its high potential, local knowledge and applicable tecgnology needed to isolate the precious content are still lacking. This study aimed to develop an effective method to get the highest possible yield of high quality extract from the Phaleria macrocarpa fruit. The method chosen was a non-destructive separation using liquid-solid extraction (leaching) operated in a continous mode by percolation method. Fruits after some pretreatment were extracted using ethanol 70% v /v with the variation of 4 extraction conditions namely: temperature (26 to 52 oC), the ratio of bed length to column diameter (4 to 6), particle diameter (0,22 to 0,90 cm), and solvent flow rate( 5 to 10 mL/min) . The experimental design used was Response Surface Method-Box-Behnken design with 3 center points. The condition of extraction were varied in order to optimize % yield and DPPH equivalent. The optimum condition were found at temperature 39 oC; lb/dk 4; particle diameter 0,22 cm; solvent flow rate 10 mL/min with 93,25% yield and DPPH equivalent of 3,21 μmol DPPH/mg crude extract.